Looking for white feathers in male western capercaillies Tetrao urogallus - M. Sarasa (Arxius de Miscel-lània Zoològica)
Unusual plumage colours are of interest for environmental and evolutionary questions. This brief article reappraised information on male western capercaillies Tetrao urogallus individuals with atypical white feathers. It was inspired by a casual observation of T. u. aquitanicus in the Pyrenees. The presence of colour aberrations has been reported for several body parts in male western capercaillies. Updated quantifications of this phenomenon and the understanding of its causal factors remain pending for this species. Monitoring individual variability in plumage in tetraonids could contribute to assessing potential signs of population deterioration in species that are currently faced with population and habitat fragmentation and subject to climate change.